The Information System of the Electronic Identity Card and Kid Identity Card Recap (Case Study of Jebres District): Sistem Informasi Rekap E-KTP dan KIA Berbasis Web (Studi Kasus Kecamatan Jebres) - Kesdu, Agvadita Ratih Palupi; Pantjarani, Ari; Naury, Chairullah (Politeknik Harapan Bangsa Surakarta, 2023)
Jebres district is one of the areas under the leadership of the local government of the city of Surakarta. Jebres subdistrict office has a function to carry out the duties of some of the authority of the city government in its work area, which includes the fields of government, economy, development, people's welfare and the development of people's lives and other public service affairs handed over by the Mayor. One of the services is public service on the collection of E-KTP and KIA. E-KTP and KIA from Surakarta City Hall are handed over to each sub-district. The list of E-KTP and KIA located in the sub-district is not inputted back into the system, so when people want to take the E-KTP or KIA but they don't have the item, they have to look in the recap list provided by the City Hall and then look back to the E-KTP place. and KIA are stored, or to the DUKCAPIL room to re-confirm that the item doesn’t exist. With the creation of this system, it will make it easier for public services to take E-KTP and KIA, and it will not take long to provide services. Based on the description of the background, it can be formulated the problem to be solved in this research is